involvement of clathrin‐mediated endocytosis and two Sid‐1‐like transmembrane proteins in double‐stranded RNA uptake in the Colorado potato beetle midgut - Cappelle, K.; de Oliveira, C. F. R.; Van Eynde, B.; Christiaens, O.; Smagghe, G. (Insect molecular biology, 2016)
RNA interference (RNAi) is a powerful tool in entomology and shows promise as a crop protection strategy, but variability in its efficiency across different insect species limits its applicability. For oral uptake of the double‐stranded RNA (dsRNA), the RNAi trigger, two different mechanisms are known: systemic RNA interference deficient‐1 (Sid‐1) transmembrane channel‐mediated uptake and clathrin‐mediated endocytosis. So far, a wide range of experiments has been conducted, confirming the involvement of one of the pathways in dsRNA uptake, but never both pathways in the same species. We investigated the role of both pathways in dsRNA uptake in the Colorado potato beetle, Leptinotarsa decemlineata, known to have an efficient RNAi response. Through RNAi‐of‐RNAi experiments, we demonstrated the contribution of two different sid‐1‐like (sil) genes, silA and silC, and clathrin heavy chain and the 16kDa subunit of the vacuolar H⁺ ATPase (vha16), elements of the endocytic pathway, to the RNAi response. Furthermore, the sid‐1‐like genes were examined through phylogenetic and hydrophobicity analysis. This article reports for the first time on the involvement of two pathways in dsRNA uptake in an insect species and stresses the importance of evaluating both pathways through a well‐devised reporter system in any future experiments on cellular dsRNA uptake.